Synthesis, characterization and catalytic activity of Sn-SBA-15 mesoporous molecular sieves - Ramaswamy, Veda; Shah, Pallavi; Lazar, Karoly; Ramaswamy, A. V. (Catalysis Surveys from Asia, 2008)
Our recent reports on the synthesis of Sn-incorporated mesoporous SBA-15 materials have been reviewed. The preparation of the samples with different Si/Sn ratios followed two procedures, the first is the post-synthesis modification of SBA-15 by impregnation with Sn chloride or acetate, and the second is the direct method in which Sn chloride was introduced in to Si precursor along with amphiphilic triblock copolymer, while varying the ratio of the synthesis gel. Detailed characterization of the Sn-SBA-15 samples by a variety of techniques shows how the synthesis procedures influence the properties of the samples that reflect on the differences in (a) the structural features, (b) morphology and textural properties, such as the pore characteristics, (c) the possible location of Sn4+ ions in the meso silica structure and their reducibility, (d) the nature of the Sn species and their the coordination sphere and (e) the acid-base characteristics. We developed a possible model for the localization of Sn species in SBA-15 pore structure for different conditions of preparation. This report includes our investigations on the catalytic properties of these Sn-SBA-15 samples in 3 industrially important reactions, viz., trans-esterification of diethyl malonate, synthesis of nopol by Prins condensation of beta-pinene with para-formaldehyde and the epoxidation of norbornene. In each of this reaction, while demonstrating the catalytic role of Sn species, we show that the requirement of the type and the environment of Sn species are different for these reactions.
Keywords: mesoporous materials; Properties of Sn-SBA-15; Sn-containing SBA-15; Sn-SBA-15 catalysts; Synthesis of Sn-SBA-15